26 Effect of Age and Gender on Outcomes Following Primary Percutaneous Coronary Intervention for ST-elevation Myocardial Infarction in a UK Tertiary Centre. (3rd June 2016) - Krishnamurthy, Arvindra; Somers, Kathryn; Burton-Wood, Natalie; Anderson, Michelle; Harland, Charlotte; Keeble, Claire; McLenachan, James; Blaxill, Jonathan; Malkin, Christopher J; Blackman, Daniel J; Wheatcroft, Stephen; Greenwood, John P
Abstract : Introduction: Techniques and pharmacotherapy for Primary Percutaneous Coronary Intervention (PPCI) continue to evolve rapidly. The West Yorkshire PPCI outcome study was established to identify important clinical and procedural variables that may impact on patient outcomes following PPCI for ST-Elevation Myocardial Infarction (STEMI). We sought to clarify the influence of age and gender on major adverse cardiovascular events (MACE), which have been variably reported, in a large consecutive patient series. Methods: Retrospective analysis of 3049 consecutive patients who underwent PPCI for STEMI between 1-1-2009 and 31-12-2011 at Leeds General Infirmary. Minimum 12m clinical follow-up data were collected for all; MACE was defined as total mortality, myocardial infarction and unplanned revascularisation. Unadjusted and adjusted analyses for total mortality and MACE were performed with Cox proportional hazards models for male (n = 2223) and female (n = 826) patients and for three age tertiles - under 60yrs (Group 1, n = 1276), 60 to 79yrs (Group 2, n = 1391) and 80yrs and above (Group 3, n = 382). Results: Females (mean 68 ± 13yrs) had significantly higher rates of total mortality and MACE compared to males (mean 61 ± 13yrs) (Table 1, Figure 1 ). However, when adjusted for age, there was no statistically significant difference in total mortality or MACE between genders (Table 2, Figure 2). Age directly correlated with total mortality and MACE. Comparison between the three age tertiles showed Group 2 was associated with a higher rate of death (HR 4.17, 95% CI 2.86–6.09) and MACE (HR 2.03, 95% CI 1.60–2.57) at 12m compared to Group 1. The highest rate of death (HR 10.53, 95% CI 7.07–15.67) and MACE (HR 3.93, 95% CI 2.99–5.17) was seen in Group 3. Conclusion: This large retrospective study has shown that whilst women appear to have significantly higher rates of death and MACE compared to men, when adjusted for age, gender was not associated with a statistically significant difference in outcomes. The difference in unadjusted outcomes may be due to the fact that women tend to present with STEMI at an older age than men. Therefore, the difference in outcomes is likely to be age-related rather than gender-related.